China English in trouble: Evidence from dyadic teacher talk. (July 2015) - Yang, Chengsong; Zhang, Lawrence Jun
Abstract: This paper problematizes the designation of China English (CE) as a developing variety of English. Fourteen Chinese tertiary English teachers participated in a discourse-based study, in which they completed, via dyadic discussion, an acceptability judgment test (AJT) that contains a selection of 10 features allegedly emblematic of CE. Examination of the teachers' conversation shows that they did not associate these features with "China English". Further analyses reveal that they tended to comment negatively on and reject those features they saw as unacceptable in standard Englishes (SEs) and accepted those they saw oppositely, due to their general alignment with SEs norms, except that on one occasion, one of them did challenge the native-speaker benchmark openly. Drawing on these findings, we argue that the notion of CE might still remain esoteric, and CE is facing a dilemma between lack of distinctness from SEs and stigmatization of its potentially most characteristic features.